Examining the Use of Project-Based Learning in Qualitative Research Course to Promote Students' Critical Thinking - Lailatul Niasari; Fatih Al Fauzi; Endah Nur Tjendani (Journey: Journal of English Language and Pedagogy, 2025)
Critical thinking is a key competency in higher education, yet many Indonesian students experience difficulties developing this skill due to the prevalence of teacher-centered instructional practices. Project-Based Learning (PjBL) offers an alternative approach by engaging students in meaningful, real-world tasks that encourage active learning. This study examines the implementation of PjBL in a Qualitative Research course and its role in supporting students’ critical thinking development. Using a qualitative case study design, the research involved five sixth-semester students from the English Education Study Program. The data were collected from students’ mini research proposals and analyzed through an interactive qualitative analysis process focusing on four dimensions of critical thinking: inference, analysis, evaluation, and explanation. The results show that PjBL promotes higher student engagement and helps learners apply theoretical knowledge to research practice. Students displayed a moderate level of critical thinking, particularly in drawing conclusions and explaining research procedures. However, limitations were identified in their ability to analyze research problems and critically evaluate relevant literature. Overall, the findings suggest that PjBL is a beneficial instructional strategy for enhancing critical thinking in qualitative research courses, provided that learning activities are designed to further strengthen analytical and evaluative skills.